Production of Hydrogen from Biomass with Negative CO2 Emissions Using a Commercial-Scale Fluidized Bed Gasifier - Tomasz Chmielniak; Tomasz Iluk; Leszek Stepien; Tomasz Billig; Marek Sciazko (Energies)
Biomass gasification, as a thermochemical method, has attracted interest due to the growing popularity of biofuel production using syngas or pure hydrogen. Additionally, this hydrogen production method, when integrated with CO2 capture, may have negative CO2 emissions, which makes this process competitive with electrolysis and coal gasification. This article presents the results of process and economic analyses of a hydrogen production system integrated with a commercial, fluidized-bed solid fuel gasification reactor (SES technology—Synthesis Energy Systems). With the use of a single gasification unit with a capacity of 60 t/h of raw biomass, the system produces between 72.5 and 78.4 t/d of hydrogen depending on the configuration considered. Additionally, assuming the CO2 emission neutrality of biomass processing, the application of CO2 capture leads to negative CO2 emissions. This allows for obtaining additional revenue from the sale of CO2 emission allowances, which can significantly reduce the costs of hydrogen production. In this analysis, the breakthrough price for CO2 emissions, above which the hydrogen production costs are negative, is USD 240/t CO2.